Terrorism and the arts
1 online resource
Keywords: "This book assesses the key definitions, forms, contexts and impacts of terrorist activity on the arts in the modern era, using historical and contemporary perspectives. Its empirical case studies include theatre, literature, music, visual art, mass media, film and the mores of 'ordinary life.' While its immediate reflective context is Islamic fundamentalist terrorism, the book reviews a broader range of definitions and counter-definitions of 'terrorism', 'state terrorism' and 'states of terror,' examining uses of the term through a series of comparative analyses. Chapters focus on the intersection of these definitional questions with heuristic analysis of art forms, cultural activities and their socio-historical contexts. This book will be of interest to scholars in art history, terrorism, politics and the media, and visual culture"--